Temporal whole field sawtooth flicker without a spatial component elicits a myopic shift following optical defocus irrespective of waveform direction in chicks - Melanie J. Murphy; Nina Riddell; David P. Crewther; David Simpson; Sheila G. Crewther (PeerJ, 2019)
Purpose Myopia (short-sightedness) is the commonest visual disorder and greatest risk factor for sight threatening secondary pathologies. Myopia and hyperopia can be induced in animal models by rearing with optical lens defocus of opposite sign. The degree of refractive compensation to lens-induced defocus in chicks has been shown to be modified by directionally drifting sawtooth spatio-temporal luminance diamond plaids, with Fast-ON sawtooth spatio-temporal luminance profiles inhibiting the myopic shift in response to negative lenses, and Fast-OFF profiles inhibiting the hyperopic shift in response to positive lenses. What is unknown is whether similar sign-of-defocus dependent results produced by spatio-temporal modulation of sawtooth patterns could be achieved by rearing chicks under whole field low temporal frequency sawtooth luminance profiles at 1 or 4 Hz without a spatial component, or whether such stimuli would indiscriminately elicit a myopic shift such as that previously shown with symmetrical (or near-symmetrical) low frequency flicker across a range of species. Methods Hatchling chicks (n = 166) were reared from days five to nine under one of three defocus conditions (No Lens, +10D lens, or −10D lens) and five light conditions (No Flicker, 1 Hz Fast-ON/Slow-OFF sawtooth flicker, 4 Hz Fast-ON/Slow-OFF sawtooth flicker, 1 Hz Fast-OFF/Slow-ON sawtooth flicker, or 4Hz Fast-OFF/Slow-ON sawtooth flicker). The sawtooth flicker was produced by light emitting diodes (white LEDs, 1.2 –183 Lux), and had no measurable dark phase. Biometrics (refraction and ocular axial dimensions) were measured on day nine. Results Both 1 Hz and 4 Hz Fast-ON and Fast-OFF sawtooth flicker induced an increase in vitreous chamber depth that was greater in the presence of negative compared to positive lens defocus. Both sawtooth profiles at both temporal frequencies inhibited the hyperopic shift in response to +10D lenses, whilst full myopic compensation (or over-compensation) in response to −10D lenses was observed. Conclusions Whole field low temporal frequency Fast-ON and Fast-OFF sawtooth flicker induces a generalized myopic shift, similar to that previously shown for symmetrical sine-wave and square-wave flicker. Our findings highlight that temporal modulation of retinal ON/OFF pathways per se (without a spatial component) is insufficient to produce strong sign-of-defocus dependent effect.